Design and measurement the RF properties of a 13MHz cavity for an RF implanter - Trịnh, Thị Tú Anh (2023)
A 13 MHz Radio Frequency (RF) cavity for an RF implanter has been designed and fabricated at the Proton Engineering Frontier Project (PEFP). It consists of a coil having a circular cross-section, accelerating electrodes that are directly coupled to the beginning and the end of the coil, and a ground electrode for the inductor. The purpose of this paper is to explain the design concept and the measurement results for the RF properties of this cavity. A resonant frequency of 12.69 MHz with critical coupling and an unloaded quality factor of 1066 were achieved, agreeing well with the simulation results. The field distribution in the cavity was measured by using the bead-pull method. The field flatness is 6.5%, which satisfies the control requirements for the field in the cavity.